Effect of SiO2 nanoparticles as lubricating oil additives on the cold-rolling of AZ31 magnesium alloy sheet. (May 2015) - Xie, H. M.; Jiang, B.; He, J. J.; Xia, X. S.; Jiang, Z. T.; Dai, J. H.; Pan, F. S.
Abstract : Magnesium alloy sheets were processed by cold rolling without lubrication and with SiO2 nanolubricant so as to investigate cold rolling performance by measuring rolling force as well as the surface roughness of the sheets. A series of ball on disc tests without lubrication and with SiO2 nanolubricant conditions were carried out to simulate the contact and sliding during the cold rolling process. The results indicate that the SiO2 nanolubricant effectively reduced the rolling force and improved the surface quality of sheets by SiO2 nanolubricant during cold rolling process. The excellent cold-rolling performances of AZ31 Mg alloy with SiO2 nanolubricant were attributed to the friction-reducing and the anti-friction mechanism was based on the deposition of nanoparticles on the magnesium alloy surfaces.